2021
DOI: 10.1108/jd-09-2021-0189
|View full text |Cite
|
Sign up to set email alerts
|

Information culture and recordkeeping: a case of Chinese enterprises

Abstract: PurposeThe purpose of this paper is to report findings from an investigation on the information culture and recordkeeping in two Chinese companies, exploring the interaction between information culture and recordkeeping.Design/methodology/approachOn the basis of systematic literature review, this research investigates the information culture and recordkeeping in two Chinese companies by conducting in-depth interviews with the staff of the two companies.FindingsThe attitude of the leadership and the staff towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Information culture and information literacy Information culture espoused in good governance of information is a crucial determinant of how individuals relate with and use information (Chen et al, 2019;Lian et al, 2021'Abukhait;Turgunov, 2022). Several empirical studies have confirmed that information culture creates conditions for collaborative learning and standardization of knowledge are created (Kolmykova and Korneeva, 2021;Lian et al, 2021). Two main dimensions characterize information culture, that is information values and norms and information behavior.…”
Section: Smallholder Maize Farmers In Ugandamentioning
confidence: 99%
“…Information culture and information literacy Information culture espoused in good governance of information is a crucial determinant of how individuals relate with and use information (Chen et al, 2019;Lian et al, 2021'Abukhait;Turgunov, 2022). Several empirical studies have confirmed that information culture creates conditions for collaborative learning and standardization of knowledge are created (Kolmykova and Korneeva, 2021;Lian et al, 2021). Two main dimensions characterize information culture, that is information values and norms and information behavior.…”
Section: Smallholder Maize Farmers In Ugandamentioning
confidence: 99%
“…Whereas most of the recordkeeping literature has been concerned with assessing whether organisations were correctly managing records in accordance with legislation and best practice standards and with finding ways of improving recordkeeping practices in organisations so that they comply with laws and standards, a growing strand of research argues that to be effective and sustainable, recordkeeping practices must be adapted to the information culture of the organisations (Oliver and Foscarini, 2020; Oliver et al, 2018; Lian et al, 2022; Frings‐Hessami & Oliver, 2022a, 2022b). Recordkeeping in an organisation is impacted by the information culture of the organisation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Oliver & Foscarini (2014, p. 11) defined information culture as “the values accorded to information, and attitudes towards it, specifically within organizational contexts”. Research has shown the importance of taking into account the context in which recordkeeping activities are performed (Oliver, 2008) and adopting a human‐centred approach to the management of information in organisations (Lian et al, 2022). The information culture of an organisation is influenced by many factors, including the national and regional culture, the organisation type, its purpose and its history, its organisational structure, the personality of its leaders and the background and skills of its employees (Oliver, 2008; Choo et al, 2008; Lian et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Scott (2019), the records management program of an organization should be by policies and procedures that handle each component of the records management program in line with operational and legal requirements. Lian, Wang, and Oliver (2021) discussed the importance of good records management practices in an organization. Good records and information governance should be in place for the organization to remain competitive.…”
Section: Effective Records Management Practicesmentioning
confidence: 99%